Combination of ShuangDan Capsule and Sorafenib Inhibits Tumor Growth and Angiogenesis in Hepatocellular Carcinoma Via PI3K/Akt/mTORC1 Pathway. (March 2022) - Ding, Wenbo; Chen, Xiuwei; Yang, Licheng; Chen, Yaping; Song, Jie; Bu, Weiquan; Feng, Bin; Zhang, Meng; Luo, Yi; Jia, Xiaobin; Feng, Liang
Hepatocellular carcinoma (HCC) is a high mortality liver cancer. The existing treatments (transplantation, chemotherapy, and individualized treatment) with limitations. However, drug combination provides a viable option for hepatocellular carcinoma treatment. A Chinese patent medicine, ShuangDan Capsules (SDC), has been clinically prescribed to hepatocellular carcinoma patients as adjuvant therapy and has shown good antitumor activity. The purpose of this study was to investigate whether SDC could improve the anti-cancer effect and mitigate adverse reactions of sorafenib on HCC in vivo. Magnetic resonance imaging (MRI), immunohistochemistry, and western blot were executed to reveal the potential mechanisms of the combination of SDC and sorafenib on HCC. Tumors appeared hyperintense on T2 sequence images relative to the adjacent normal liver in MRI. Combination of SDC and sorafenib inhibited the progression of DEN (Diethylnitrosamine)-induced HCC. In the HepG2 xenografts model, sorafenib plus SDC exhibited greater suppression on tumor growth than individual treatment accompanied with decreased expression of VEGF, VEGFA, Ki67, CD31 and increased expression of caspase-3. Furthermore, PI3K/Akt/mTORC1 pathway was inhibited by co-administration. Sorafenib monotherapy elicited hepatotoxicity for specific expression in the up-regulated level of aspartate transaminase (AST) and AST/glutamic-pyruvic transaminase (ALT) ratio, but the co-administration could remedy this adverse effect. These dates indicated that the combination of SDC and sorafenib might offer a potential therapy for HCC.